High Efficacy of Stem Cell Mobilization With Etoposide+Cytarabine Plus G-CSF in Patients With Multiple Myeloma - Zhu, Zhijuan; Li, Xiaofan; Liu, Yiping; Chen, Ping; Chen, Xianling; Li, Hua; Huang, Jiafu; Chen, Yuanzhong; Li, Nainong (Frontiers in Oncology, 2022)
Background Efficient mobilization of CD34+ hematopoietic stem cells plays a vital role in successful autologous stem cell transplantation (ASCT) in patients with multiple myeloma (MM), especially in cases with high-risk cytogenetic recommended for tandem ASCT. However, the optimal mobilization strategy remains a matter of debate in the era of lenalidomide. The combination of etoposide with Cytarabine plus G-CSF as a novel mobilization regimen in MM has not been reported previously. Methods This research retrospectively studied mobilization efficacy and safety using etoposide combined with Cytarabine (etoposide 50–100 mg/m2, qd d1–3; AraC 0.5 g/m2, q12h d1 3) plus G-CSF (5 µg/kg/day, from d5 until the day of apheresis) in 128 patients with MM. 70(54.7%) patients received lenalidomide-based induction regimens treatment Results A median of 27.75×106 CD34+ cells/kg was collected in the first apheresis, and 28.23×106 CD34+ cells/kg were collected overall. Of the 128 patients, all achieved adequate collection (≥2×106 CD34+ cells/kg), 121(94.5%) achieved optimal collection for single ASCT (≥5×106 CD34+ cells/kg), and 114(89.1%) harvested optimal collection for tandem ASCT (≥10×106 CD34+ cells/kg). In particular, the target yield of optimal collection for tandem ASCT was reached in 82.8% (106/128) by a single apheresis procedure. 14 patients obtained deeper response post mobilization. In multivariate analysis, cycles of prior chemotherapy independently affected the optimal achievement of CD34+ cells (p=0.004, OR 0.695, 95% CI 0.544 0.888). Previous lenalidomide exposure did not significantly impair CD34+ cells collection. Although 68% episodes of antibiotic usage were observed, no severe infection or treatment-related mortality occurred. Conclusion Stem cell mobilization with Etoposide + Cytarabine plus G-CSF was highly efficient and safe in patients with MM, which could be considered in high-risk MM patients who were referred for tandem ASCT.